EDUCATION OF ELDERLY PEOPLE AS AN EDUCATIONAL TREND OF THIRD MILLENNIUM - Олена Аніщенко (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2021)
The publication is devoted to the analysis of some features of elderly education development. There is a substantiation of the urgency of the raised problem. Emphasis is placed on the fact that the education of elderly people is an indicator of the development level of cultural, moral, scientific and technical potential of the country. The focus is on the essential aspects of hierargoics as a science. The need to develop a new perception philosophy of population aging and strategies to ensure old age in the life cycle of each individual is emphasized. The necessity of implementation of the complex state policy on education of elderly people, development and implementation of multivector programs for the outlined category of adult population is substantiated. It is emphasized that universities of the third age function as social projects in all regions of Ukraine. In the article highlighted the development of the state target program "Universities of the third age: it is never too late to study"; creation of the third age virtual universities (online universities); scientific substantiation of organizational and pedagogical conditions of creation and functioning of the third age universities; strengthening intersectoral / interagency cooperation and expanding networking in the world of elderly at the local and national levels. It was emphasized that institutions for the education of older adults should promote the development of their social activity, overcome isolation, loneliness and provide comprehensive socio-cultural adaptation and rehabilitation. Special attention is paid to the issue of pedagogical staff training for the teaching of the elderly. The expediency of interdisciplinary research on the theory and practice of senior adult education is substantiated. It is determined that a perspective area of further research is the problem of scientific and methodological support for the elderly education.